Pengaruh Pemberian Reward terhadap Kinerja Karyawan pada CV. Pintu Mas Kota Sorong - Erlinda, Desy; Renouw, Ade Andriani; Sapari, Lili. S. J. (Attractive : Innovative Education Journal, 2022)
Human resources are certainly something that cannot be separated from the operations of a company or organization. Of course, human resources have a very important role in the journey of a company because human resources are the driving force for the company's production activities. Employee performance is something that must be improved by companies where the economy is currently growing rapidly, causing competition, one of which is the industrial sector that is engaged in CV.Pintu Mas Sorong City, one of the things that can improve employee performance is the provision of rewards to employees. The purpose of this study was to determine the effect of rewards on employee performance at CV. Pintu Mas Sorong City. Sampling was carried out using a population sample, namely, all populations were involved to become a sample of 34 respondents. The type of research used is quantitative with simple linear regression analysis and T-test. From the results of calculations using simple linear regression analysis obtained the following regression equation : Y = 7,555 + 0,576X. Obtained from the Reward variable value of 0,576 implies that every change and one percent addition to the Reward variable, then the Employee Performance variable will be increased by 0,576. The result of t-test analysis shows that partially the reward variable has a positive and significant effect on employee performance with a significant value of 0,00<0,05, score tcount 3,958 > from ttable 2,035 which means Ha is accepted and Ho is rejected. Based on the analysis and discussion, it can be concluded that reward has a significant effect on employee performance at CV. Pintu Mas Sorong City. Keywords: Employee Performance, Give Reward, Effect Reward